2003
DOI: 10.1108/09593840310463032
|View full text |Cite
|
Sign up to set email alerts
|

Jordan and ICT‐led development: towards a competition state?

Abstract: This paper describes Jordan's strategy to develop a strong ICT sector that will be internationally competitive. This strategy is analysed in two ways. First, by a comparison with two countries, Ireland and Singapore, with similarities as nation states and which are widely seen as successful in promoting and sustaining strong ICT sectors. Second, through an analysis of Jordan as a competition state where the role of the state is being redefined so as to implement policies in a globalising world. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…Electronic method was used in order to get individuals who are educated, Web users and likely users of e-democracy platforms. Research in Jordan found that educated people are early adopters of the Internet and potential users of e-democracy services (Al-Jaghoub and Westrup, 2003). E-mail message containing the link to the Google Form, and the essence of the survey was sent to the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic method was used in order to get individuals who are educated, Web users and likely users of e-democracy platforms. Research in Jordan found that educated people are early adopters of the Internet and potential users of e-democracy services (Al-Jaghoub and Westrup, 2003). E-mail message containing the link to the Google Form, and the essence of the survey was sent to the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…This research finding is compatible with other research studies that reviewed different ICT initiatives development in Jordan indicating that most government agencies are facing capacity problems. This is due to complicated existing processes and to working culture (Al-Jaghoub & Westrup, 2003;Kulchitsky, 2004;Ciborra, 2005;Ciborra & Navarra, 2005;Navarra, 2006). However, most of the ICT based initiatives around the world, including the most successful, are facing similar problems to varying extents depending on the country's profile.…”
Section: Strategic Issues Affecting Ict Developmentmentioning
confidence: 99%
“…The Hashemite Kingdom of Jordan is a developing, middle-income country, which also has scarce natural resources but with highly educated human resources. As a result, ICTs are being seen by the Jordanian government to provide an exceptional opportunity for the country to become competitive in this area (Al-Jaghoub and Westrup, 2003). In response, Jordan undertook aggressive steps in order to launch its major ICT based initiatives with the aim of transforming the country to eJordan (REACH, 2000;Ciborra & Nevarra, 2005).…”
Section: Research Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has scarce natural resources, Jordan has some competitive advantageous factors, which include the following (REACH, 2000, Al-Jaghoub and Wetrup, 2003, Department of statistics, 2006, and Jordan, the official site of the Jordanian E-Government, 2008):…”
Section: Sample and Study Populationmentioning
confidence: 99%